(untitled) (Journal of Guidance and Counselling Studies, 2024)
This study examined the impact of innovative support on learners’ success in open and distance learning at universities in Nigeria. The study employed descriptive survey research design for the study. Three research questions guided the study and two null hypotheses were tested. Sample size of the study was ODL students of Lagos State University study centre. Questionnaire was used as the instrument to guide the conduct of the study. Descriptive statistics were adopted to analyse the demographic data while Pearson Product Moment Correlations was used to test the null hypotheses at .05 level of significance. The study revealed that innovative support is very much required in learners’ academic success in Nigerian ODL universities. There is technological impact on learner’s success and technology does have significant improvement on the integrity of online testing. The study concluded that innovative supports are very much required for learners’ academic success. Therefore, the study recommends that to provide students with the skills needed in the current ODL environment, universities lecturers should adopt innovative approaches of instruction delivery, and testing, institutions should closely oversee and guarantee complete adherence to the application of innovative support for instructional deliveries and government funding should be made available for the acquisition and sufficient provision of the facilities and equipment required for cutting-edge instruction.